(untitled) (Studia Prawnicze / The Legal Studies, 2006)
Znany bon mot „Władzy potrzebna jest wiedza, tak jak pijakowi latarnia, ale nie po to, by mogła lepiej widzieć, ale by mogła się na czymś oprzeć", używany najczęściej jako ironiczny, powszechnie znany, pogardliwy stosunek „władzy" do ścisłego poznania, obowiązywał paradoksalnie w Czechosłowacji i w Republice Czeskiej podczas przeprowadzania reformy administracji publicznej, a szczególnie podczas procesu odnowy demokratycznego samorządu terytorialnego, w całej krasie i bez odcienia ironii. Wyjątkowy wpływ i znaczenie dla reformy miała Europejska Karta Samorządu Terytorialnego, przyjęta przez Radę Europy w Strasburgu 15 października 1985 r. Europejska Karta Samorządu Terytorialnego, zwana dalej Kartą, przez większą część lat dziewięćdziesiątych była bowiem podstawowym argumentem i instrumentem, stanowiącym dla nas faktycznie jedyne oparcie przy forsowaniu europejskiego tradycyjnego modelu samorządu terytorialnego. Karta ta dobrze służyła i pomagała podczas konfrontacji z modelem jednostronnie ekonomicznym lub transformacją społeczną, ukierunkowaną na gospodarkę. Public administration is one of the decisive factors of assurance of extemal economic and social competitiveness of Czech society as well as - in the projection of its activities into the operatin of the whole public sector - a significant factor of maintaining inner social peace in its framework. In the first place public administration in the Czech Republic is always controlled by analogous pressures as public administrations in other countries brought about by globalization, the development of information technology, the evolution of citizens’ participation as well as by the individualization of life, increasing complexity and intermediation of the influence of the individiual ori the administration of public affairs and the growth of the possibilities of influencing public opinion. Contemporary public administration systems react to these pressures particularly by decentralization and regionalization of administration, opposing the restrictions of the role of the national state by the development of mediating activities in which the superior role of public administration in the regulation of social life is supplemented with the more generał concept of service to citizens as an organizer of social dialogue. Secondly it involves the confrontation with the practical requirements of harmonization of the content and the system of the Czech public administration with the generally recognized requirements imposed on the operation of public administration in European countries, such as the requirements of good governance, public service, accountability to the public and the emphasis on social effectiveness, cost effectiveness and transparency of public admninistration connected therewith. Of extraordinary impact on and significance for the restoration of democratic territorial self-government in particular in Czechoslovakia and subsequently in the Czech Republic was the European Charter of Local Self-Government ("the Charter"), adopted by the Coucil of Europe in Strassbourg on 15 October 1985. In the Czech Republic the Charter contributed to the assertion of the traditional model of European territorial administration in the confrontation with the instrumentarium of onesidedly economically oriented transformation of society of which public administration reform formed a considerable and continuously neglected part. In the Czech Republic the Charter entered into force on 1 September 1999. Its adoption was preceded by a long period of debates and opposing reactions in the course of which the Charter was submitted to the legislative assembly several times even during the federal period. The negative reactions were based mostly on the generally contrary attitude of the decisive part of the political spectrum to decentralization and enhancement of the role of self-govemment on the one hand and to the broadening of citizens’ participation in the administration of public affairs and direct democracy on the other hand. That is why the Charter could be adopted only towards the end of the nineties w hen these obstacles had been partly overcome. However, the Charter exercised positive influence already on the origin and conception of the historically first restored communal order, viz. the Act No. 367/1990 Coll. (The Communal Act). The topic important at present is the research of the extent at which the principles of the Charter are really applied in legislative practice. Particularly poor application on local level can be observed in the proportion of direct and representative democracy. The new Communal Act (Act No. 128/2000 Coll.) extended significantly the possibilities of active citizens participation in the decisionmaking of communal self-government. The actual exercise of the citizens’ legal rights, however, is made difficult by the procedural rules of a number of communal and city councils. Analogously the new codificaion of local referendum (Act No. 222/2000 Coll.) has made the organization of local referenda significantly more difficult by increasing the required number of citizens entitled to voting in the referendum from one quarter to one half of all citizens entered in voters’ registers and the consent of more than half of participating voters for the referendum result to be valid. The first amendment of the Regional Act (Act No. 129/2000 Coll.) eliminated the possibility of regional referendum altogether.